Synthesis of pseudobrookite titanium oxynitride Ti3−δO4N films by laser chemical vapor deposition. (June 2015) - Ito, Akihiko; Joo, Hye-Sook; Kim, Taek-Soo; Goto, Takashi
Abstract: Pseudobrookite Ti3−δ O4 N films were prepared by laser chemical vapor deposition with titanium tetraisopropoxide and NH3 as precursors. By increasing the deposition temperature from 964 K to 1294 K, the phase composition of the films changed from TiO2 to Ti3−δ O4 N and subsequently to Ti(O, N). Ti3−δ O4 N films with fine columnar grains were obtained at 1030 K and at a total chamber pressure of 0.6–0.8 kPa. The deposition rate of these films reached 7 μm h −1 . Highlights: Pseudobrookite Ti3−δ O4 N films were prepared by laser CVD using TTIP and NH3 . High-speed deposition of the Ti3−δ O4 N film (7 μm h −1 ) was demonstrated. Crystalline Ti3−δ O4 N solid films consisted of fine columnar grains.